Association of necrophilous beetles (Coleoptera) with rat carcasses in a semi-arid area, Northeastern Brazil - Santos, Daniella de Souza; Santos, Wellington Emanuel dos (ENTOMOTROPICA, 2016)
The association of beetles with rat carcasses exposed in a semi-arid area was examined. Samplings took place during rainy and dry seasons in an herbaceous-shrub Caatinga layer. The families represented; Histeridae, Scarabaeidae and Tenebrionidae, were collected in all seasons and vegetation layers. Four decomposition stages were recognized, in which the black putrefaction and the dry decay were the most attractive to Histeridae and Scarabaeidae, respectively. Considerations about ecology, behavior and use of theses beetles in forensic entomology are also presented.